BUSINESS TO BUSINESS (B2B) E-MARKETPLACE SEBAGAI MEDIA PROMOSI PRODUK USAHA KECIL DAN MENENGAH (UKM) - Mansur Mansur (BBM (Buletin Bisnis & Manajemen), 2015)
B2B e-Marketplace is a media the promoted actor for Small and MediumEnterprises (SMEs) that has play role important to realize economic nationalstructure in growing and developing SMEs ability to be strong and independentbusiness, and can to increase build of region, employment generation, equityrevenue and growing of ASEAN economic comminity. This research purposed todesign website as media promoted product for SMEs and supplier at Bengkalisgoverment used concept B2B e-Marketplace. Application B2B e-Marketplace stakethe used developing approach such as system waterfall. The result of this researchis design website e-Marketplace web-based integration, and can to giveadvantage for SMEs and supplier in to spread reach access promoted product witheasy and cost relative cheap until it can increase competitiveness of businessestowards economic community of ASEAN.Keyword : B2B e-marketplace, product promotion, smes, supplier